The economic status of Asian Americans before and after the Civil Rights Act - Harriet Duleep; Seth G. Sanders (Institute for the Study of Labor (IZA), 2012)
In contrast to their relative standing in today's labor market, in 1960 U.S.-born men in all Asian groups earned substantially less than comparable whites. We explore explanations for the wage gap and find that all of the variables that might plausibly account for it, such as Asian/white differences in schooling, labor force participation, entrepreneurial and agricultural employment, English proficiency, enclave activity, and foreign-born parentage, have either no effect or only modest effects on the 1960 wage gap and its subsequent reduction. Our findings suggest that anti-Asian labor market discrimination was the predominate cause of the 1960 wage gap and that most of the 1960 to 1980 improvement in the relative wages of U.S.-born Asian men stemmed from a decline in anti-Asian discrimination. Although much of the policy focus of the civil rights era was directed at reducing discrimination against blacks, our findings suggest a prominent post-Civil Rights Act labor market effect for Asians. If these results hold up to further scrutiny, one interpretation is that the Civil Rights Act and accompanying activities, and/or concomitant changes in societal attitudes, benefited all minorities.
Keywords: J48; J71; J78; J15; J18; 330; anti-discrimination legislation; minority economic progress; Asian Americans; Civil Rights Act; Asiaten; Gleichbehandlungsrecht; Wirkungsanalyse; Lohndifferenzierung; Schätzung; USA